The The Application of the Group Investigation Model as an Effort to Strengthen Students' Democratic Attitudes in the Pancasila Education Course - Ridwan, Ahmad; Murdiono, Mukhamad; Cathrin, Shely; Sataroh, Sindy; Marzuki, Marzuki (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study aims to analyze and describe the application of the group investigation model to strengthen students' democratic attitudes in the Pancasila Education course. This research uses a qualitative approach with a descriptive research type. Data were obtained through observation, interviews, and documentation. This research was conducted at Yogyakarta State University in the undergraduate department of education management in the odd semester of the 2023/2024 academic year, involving 46 students as the main informants. The results showed that the application of the group investigation model in the active learning process, both in class and through WhatsApp groups, was facilitated by a discussion sheet containing responses, suggestions, and questions that had to be filled in by several groups of listeners. The discussion was conducted after the presenting group delivered its topic, where the listening group gave responses to the presenting group. This democratic attitude emerges due to students' active participation in the learning forum, which includes freedom to participate, freedom of expression, and the development of collaborative attitudes. Thus, the group investigation model improves the understanding of the material and shapes students' characters to be more democratic and collaborative in their interactions with others.